Differences in Anti-Müllerian Hormone Levels Before and After Platelet-Rich Plasma–Based Ovarian Rejuvenation in Patients with Premature Ovarian Insufficiency - Aprillia Tamitha Hoata; Kadek Ayu Restu Paharbumi; Ida Bagus Putra Adnyana; Anom Suardika; Made Darmayasa; Kadek Agus Wijaya; Made Angga Diningrat (Journal La Medihealtico, 2026)
Premature Ovarian Insufficiency (POI) is defined as a decline in ovarian function before the age of 40, with an estimated prevalence of approximately 3.7%, particularly higher in countries with low to medium Human Development Index (HDI). POI can negatively affect both physical and psychological health in women. Anti-Müllerian Hormone (AMH) is widely recognized as a biomarker to assess ovarian reserve. Recently, Platelet-Rich Plasma (PRP) therapy has been investigated as a novel approach to enhance AMH levels and rejuvenate ovarian function in POI patients. To evaluate the effect of PRP-based ovarian rejuvenation therapy on AMH levels in women with POI. This retrospective observational analytic study involved 33 women diagnosed with POI who underwent PRP ovarian rejuvenation therapy at Bali Royal Hospital between 2022 and 2024. Total sampling was employed, and secondary data were obtained from patient medical records. Data were analyzed using univariate and bivariate methods, specifically paired-sample t-tests. The study included 33 women with a mean age of 35.62 ± 5.68 years. The mean baseline AMH level was 0.53 ± 0.34 ng/mL, which increased to 0.66 ± 0.46 ng/mL three months after PRP therapy. Statistical analysis demonstrated a significant increase in AMH levels following PRP treatment (p ≤ 0.05). A statistically significant difference in AMH levels was observed before and three months after PRP-based ovarian rejuvenation therapy in women with POI treated at Bali Royal Hospital during the 2022–2024 period. These findings indicate that PRP may represent a promising adjunctive therapy for improving ovarian reserve in patients with POI.